El Excentrico, 1967-12-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
December 5, 1967 [5 de diciembre de 1967] No volume or issue number. Cover has a picture of a toddler Rebecca Kim Cook eating a cake. The headline reads, "Rebecca Kim Cook, essence of obedience - Reason: Christmas Approaching."